PENGGUNAAN INSTAGRAM @bujangdarapku SEBAGAI MEDIA PROMOSI PEMILIHAN BUJANG DARA KOTA PEKANBARU - Ricko Afaldi Putra; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Popularity and high usage of Instagram is one of the reasons of bujang dara pekanbaru association to use Instagram as a promotional tool in selection of bujang dara pekanbaru in hopes of getting the best finalist in every year. the purpose of this research was determining Instagram usage as a promotional media in selection of bujang dara pekanbaru.This research used qualitative methode by descriptive approach. Informan of this research is Public Relation of Bujang Dara Pekanbaru association, admin of @bujangdarapku and Department of tourism Pekanbaru, Dara Pekanbaru 2016th, Finalist of Bujang Pekanbaru 2014th who were selected by using purposive technique. Data collection technique used observation, interview and documentation.The result of research showed that Instagram account @bujangdarapku doing some basic aspects of communication using Instagram, 6 of the 7c Framework that is context and content as attract Instagram user and determine the target. Connection provide convenience acces to users to get information, communication shows a positive interaction between admins adn followers, while commerce encourage cooperation that built benefit for Bujang Dara Pekanbaru. And sponsor and community dissemminate information personal and broadly .Keyword: Instagram, Promotion, Bujang Dara.